Seeing and Not Seeing the Land: An Observability Gradient in Farmers' Place-Based Environmental Knowledge and Its Implications for Geography Education - Syamsunardi; Hasriyanti; Tri Salsabila Putri (CV Bumi Spasial, 2026)
This study maps the structure of place-based environmental knowledge among shallot (Allium cepa L. var. aggregatum) farmers in Bubun Lamba Village, Enrekang Regency, Indonesia, and derives design principles for place-based geography learning. A descriptive quantitative survey was administered to 36 active shallot cultivators, using a 22-item instrument covering eleven agro-environmental domains, complemented by semi-structured interviews. Self-assessed knowledge was uniformly strong in procedural, directly observable domains, fertilisation (M = 9.6), harvesting (M = 9.5), and irrigation (M = 9.0), but markedly weaker in the edaphic domain (M = 5.0), the only domain whose key variables (pH, nutrient availability) are latent and instrument-dependent. Interview data show that farmers substitute a temporal heuristic, liming after four to five consecutive cropping cycles, for direct measurement of soil acidity. We interpret this distribution as an observability gradient: informally acquired environmental knowledge is robust where phenomena are visible and feedback is rapid, and attenuates sharply where phenomena are latent and feedback is delayed. This gradient functions as a diagnostic map for learning design: place-based geography education should not rehearse what communities already master through practice, but should target latent domains by making invisible processes perceptible through instrumentation, visualisation, and modelling. Implications for community geo-education, contextual school curriculum materials on the pedosphere and food security, and teacher fieldwork design are discussed.